Das Augenblickchen und das Stückelchen.: Die Diminutivsuffixe -chen und -elchen diesseits und jenseits der deutsch-luxemburgischen Staatsgrenze - Frank, Marina (Linguistik Online, 2019)
This study deals with the diminutive suffixes -chen and -elchen in the Moselfranconian base dialects on both sides of the Luxo-German state border. It covers the entirety of the state of Luxembourg as well as the Moselfranconian dialects of German within the area of investigation of the Linguistic Atlas of the Central Rhine (MRhSA). The study examines the Wenker questionnaires from the end of the 19th century that were collected by Georg Wenker and John Meier as well as a second and third series of data in the form of Wenker questionnaires that were collected in the 1920s by Richard Huss and data from the MRhSA collected in the 1980s. Building on Edelhoff (2016), who analyses the development of diminutive plurals and plural diminutives in German and Luxemburgish dialects, and Edelhoff (2017a, 2017b) this study provides a closer look on the forms of the diminutive suffix in the singular, particularly of the two lexemes Augenblickchen ,moment.dim’ and Stückchen ,piece.dim’. It is not only a matter of general concern to show the spatial distribution of the suffix forms ‑chen and ‑elchen in the base dialects, but it attempts to shed some light on language-dynamic processes taking place. Specifically, this involves taking a closer look at the following questions: 1) Can language change in the direction of the prestige variety of Central Luxemburgish on the Luxemburgish and in the direction of Standard German on the German side of the state border be shown, in the sense of the Language Dynamics Approach (Schmidt/Herrgen 2011)? 2) Can Edelhoff’s (2016) constatation that the state border has become a dialect border with regard to the use of the diminutive plural suffix also be demonstrated for the diminutive singular suffix variants ‑chen and ‑elchen? 3) Is there geolinguistic evidence for the thesis that the morphological variant ‑elchen is a fusion of the suffixes -lein and -chen? This article provides a preliminary answer to these questions and sketches some lines of inquiry for future research.